Immunological Signaling During Herpes Simplex Virus-2 and Cytomegalovirus Vaginal Shedding After Initiation of Antiretroviral Treatment. (6th April 2016) - Nason, Martha C.; Patel, Eshan U.; Kirkpatrick, Allison R.; Prodger, Jessica L.; Shahabi, Kamnoosh; Tobian, Aaron A. R.; Gianella, Sara; Kalibbala, Sarah; Ssebbowa, Paschal; Kaul, Rupert; Gray, Ronald H.; Quinn, Thomas C.; et al.
Abstract: Vaginal proinflammatory cytokine expression during herpes virus reactivation was examined in human immunodeficiency virus-infected women before and after initiation of antiretroviral therapy (ART). Vaginal swabs were screened for levels of cytokines interleukin (IL)-1β, IL-2, IL-4, IL-6, IL-8, IL-10, IL-12p70, IL-13, tumor necrosis factor (TNF)-α, and interferon-γ. The relative risk (RR) of herpes simplex virus-2 or cytomegalovirus (CMV) shedding being associated with cytokine levels above the median were estimated. Herpes simplex virus-2 shedding was significantly associated with higher levels of IL-6 (RR = 1.4, P = .003) and TNF-α (RR = 1.3, P = .010), whereas CMV shedding was associated with higher IL-6 (RR = 1.3, P = .006) and IL-2 (RR = 1.4, P = .01). The association of viral shedding with higher IL-6 levels suggests that herpes virus reactivation may be playing a role in immune activation after ART initiation.